PENGARUH SPIRITUALITAS KERJA KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA SATUAN POLISI PAMONG PRAJA PROVINSI BANTEN - Engga Jalaludin; Janusi Waliamin (STIE Mahardhika, 2022)
This study aims to analyze the effect of work spirituality, organizational commitment and employee performance using a sample of 81 employees of the Civil Service Police Unit of Banten Province who are already civil servants. The research design uses quantitative research methods and the analysis used is SEM-PLS analysis using WarpPLS software. This study found that: Positive and significant influence between work spirituality has a positive and significant effect on organizational commitment, as well as organizational commitment has a positive and significant effect on employee performance.